2019
DOI: 10.1021/jacs.9b05973
|View full text |Cite
|
Sign up to set email alerts
|

Perspective of Chiral Colloidal Semiconductor Nanocrystals: Opportunity and Challenge

Abstract: Chiral colloidal semiconductor nanocrystals (NCs) are an emerging type of chiral materials. These chiral NCs exhibit unique quantum confinement-determined optical activity and have aroused much interest in the multidisciplinary fields of chemistry, physics and biology. Herein, the state-of-the-art progresses of their rational synthesis, fundamental understanding and potential application are summarized. In addition, a personal view about the future development of chiral semiconductor NCs is offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
98
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(100 citation statements)
references
References 87 publications
1
98
0
1
Order By: Relevance
“…3f-h), and no significant direct contribution arises from chiral organic cations to the associated band edge or excitonic transitions. The CD bands in chiral NPB can originate from the coupling of dipole transition moments in the inorganic framework and the chiral organic spacer cations (the chiral screening medium surrounding the inorganic framework), as previously observed in inorganic semiconductor nanocrystals capped with chiral surface ligands 19 . The same dipolar interactions with the chiral, organic screening medium can induce excitonic CD signals in R-and S-MBPI despite their nominally centrosymmetric inorganic layers 18,27 , thus suggesting that an induced CD does not always imply substantial chirality transfer from organic to inorganic layers.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…3f-h), and no significant direct contribution arises from chiral organic cations to the associated band edge or excitonic transitions. The CD bands in chiral NPB can originate from the coupling of dipole transition moments in the inorganic framework and the chiral organic spacer cations (the chiral screening medium surrounding the inorganic framework), as previously observed in inorganic semiconductor nanocrystals capped with chiral surface ligands 19 . The same dipolar interactions with the chiral, organic screening medium can induce excitonic CD signals in R-and S-MBPI despite their nominally centrosymmetric inorganic layers 18,27 , thus suggesting that an induced CD does not always imply substantial chirality transfer from organic to inorganic layers.…”
Section: Resultssupporting
confidence: 59%
“…Chiral organic cations have been recently employed in 2D HOIPs, resulting in ferroelectricity 16 and chiroptical properties such as circular dichroism and circularly polarized luminescence 17,18 . Notably, the inorganic-related chiroptical activity in these already reported HOIP systems is evidently an optically induced phenomenon caused by dipolar interactions with chiral cations 19,20 , and thus, the chain of evidence for structural chirality/asymmetry transfer to the inorganic layers remains incomplete if solely based on chiroptical spectroscopies. Indeed, we find (as will be discussed later) that the introduction of a chiral organic cation in 2D HOIPs does not necessarily imply a significant degree of structural chirality within the inorganic framework.…”
mentioning
confidence: 97%
“…Local modification by chiral ligands has been extensively investigated in semiconductor nanocrystals. [240] Due to the strong excitonic behavior of sub-5-nm quantum dot (QD) systems, significant effects of chiral molecules on chiroptical response have been observed. Several origins have been suggested: the simplest suggested origin is the coupling between electric fields of QDs and chiral molecules present on the surface without any structural changes.…”
Section: Chiral Geometry Of Inorganic Crystalsmentioning
confidence: 99%
“…The TEM images showed that QD533 was encapsulated inside the L-ZIF particles while the high-resolution TEM (HRTEM) image indicated that the original crystal structure of QD533 was preserved. These results illustrated that the detected CPL signal of chiral ZIF ⊃ QD533 resulted from the induced chirality by confined chiral environment from chiral ZIFs [58,59]. In addition, through tuning the mass ratio of five kinds of QDs loaded in chiral ZIF, chiral ZIF ⊃ QDs with white circularly polarized light emission also could be obtained in the solid state.…”
Section: Tunable Cpl From Qd-loaded Chiral Mofsmentioning
confidence: 78%